An experiment on bribery, tenure duration, and punishment severity in the Indonesian public finance context - Nugroho, Wisnu Setiadi; Winardi, Rijadh Djatu; Wijayanti, Amanda; Permana, Yudhistira Hendra; Sanjaya, Muhammad Ryan (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
Against the backdrop of increasing concern over corruption, this study delves into a laboratory experiment investigating the intricate dynamics of bribery concerning the duration of official tenures and the efficacy of punitive measures. Experimental methods prove pivotal in unraveling the complexities inherent in corrupt behaviors. The study unfolds a compelling pattern, shedding light on the interplay between public officials and civilians, particularly emphasizing the impact of officials' tenure duration on bribery. It brings forth a crucial correlation between familiarity with officials and a heightened likelihood of bribery, with extended tenures amplifying this susceptibility. The concept of